Effect of electrospun PPENK nanofiber loaded with ZnO nanowires on the mode Ⅱ fracture toughness, flexural properties and ILSS of CF/poly(phthalazinone ether ketone) composites. (September 2022) - Zhang, Yu; Liu, Cheng; Jia, Hang; Qiao, Yue; Dang, Xinxin; Weng, Zhihuan; Chen, Yousi; Zou, Jiaxuan; Jian, Xigao
Abstract: The weakness of easy delamination for the laminated composites always limits their wide application. In this work, the poly(phthalazinone ether nitrile ketone) (PPENK) multi-scale nanofibrous veils loaded with ZnO nanowires (ZnO@PPENK) were prepared and incorporated into the interlayer of carbon fiber reinforced poly(phthalazinone ether ketone) (PPEK) laminates (CF/PPEK). The structures and morphologies of ZnO@PPENK veils, the mode II interlaminar fracture toughness, and in-plane properties of ZnO@PPENK/CF/PPEK laminates were characterized. The results show that due to the introduction of PPENK interleaving veil, the mode Ⅱ interlayer fracture toughness of the laminated composite increased from 1238 J/m 2 to 1769 J/m 2 (an increase of 43%), and after loading ZnO nanowires, it further increased to 2618 J/m 2, an increase of 112% compared with CF/PPEK. Moreover, the flexural modulus of ZnO@PPENK/CF/PPEK composite was slightly increased by about 10%(115 GPa), and the interlayer shear strength was improved to 78 MPa, about 31% higher than that of CF/PPEK. These results provide a new idea for interlayer materials used for interlayer reinforcement of carbon fiber reinforced polymer composites. Graphical abstract: Image 1 Highlights: A new type of multi-scale electrospinning interlaced veil (ZnO@PPENK) was fabricated. The GⅡC and ILSS of ZnO@PPENK/CF/PPEK laminate were significantly improved. The toughness was enhanced by the synergistic effect of PPENK and ZnO nanomaterials.